High-electric-contact matching electric heating material for bearing and deicing integrated composite material wing as well as preparation method and application of high-electric-contact matching electric heating material
By using conductive fiber Buga nanocarbon materials in aircraft electric thermal protection/deicing systems, the problems of poor thermal stress and processing performance of existing electric heating materials are solved, and more uniform thermal conductivity and higher impact and fatigue resistance are achieved.
Patent Information
- Application Number
- CN202411831619.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-12
AI Technical Summary
In existing aircraft electric thermal protection/deicing systems, the electric heating material has problems such as thermal stress, structural thermal mismatch and poor processing performance, which is difficult to meet the needs of aviation materials' impact resistance and fatigue resistance.
The fiber cloth formed by conductive fibers is used as the toughened phase and the dominant phase. By applying nanocarbon materials, including carbon nanotubes, graphene oxide and carbon powder, to the fibers, to form an integrated composite material to improve the thermal conductivity of the material.
It realizes that the heating and conduction of electric heating materials is more uniform, improves the performance of aircraft electric heating/deicing systems, and meets the needs of impact resistance and fatigue resistance of aviation materials.
Smart Images

Figure CN119521474A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aircraft electrothermal anti-icing / deicing, and in particular to a high-electrical contact matching electrothermal material for a composite wing with integrated deicing, and a preparation method and application thereof. Background Art
[0002] Aircraft icing refers to the phenomenon of ice accumulation on certain parts of the aircraft surface. It is mainly formed by supercooled water droplets in the clouds or supercooled rain in precipitation hitting the aircraft body and freezing, or it can be formed by water vapor condensing directly on the surface of the aircraft. Aircraft icing can easily cause icing if the aircraft flies in the clouds for too long. Aircraft icing can have a serious impact on flight safety. When ice accumulates on the aerodynamic surface of the aircraft, the impact on aerodynamics is very large. Wind tunnel tests have shown that when there is half an inch of ice accumulation on the leading edge of the wing, it will reduce lift by 50% and increase drag by 60%. The speed of icing is very fast. Sometimes in severe icing conditions, the thickness of ice accumulation can reach 2-3 inches within 5 minutes. The most serious icing conditions generally occur when flying outside the clouds and encountering rain at freezing temperatures.
[0003] There are four methods for aircraft deicing at present: chemical solution deicing, gas-heat deicing, mechanical deicing and electric deicing. 1. Chemical solution deicing is to spray antifreeze on the icy surface of the aircraft for deicing and deicing. Antifreeze is a chemical liquid with a very low freezing point. It lowers the freezing point of water and melts the ice layer that has been formed. Usually, when the aircraft stays on the ground and freezes, it is deiced by spraying with a deicing vehicle. Spraying chemical reagents on the ground not only pollutes the environment to a certain extent, but can only be implemented on the ground, which has certain limitations. 2. Gas-heat deicing is to introduce a hot air source into the wings, the front edge of the tail wing and other parts that need to be deiced to prevent ice. Deicing through engine bleed air increases the burden on the engine. 3. Mechanical deicing refers to installing a layer of expandable rubber tube with airbags on the front edge of the wing. Usually, these tubes and airbags are close to the wing. After freezing, the tubes and airbags are charged and discharged to produce periodic expansion and contraction. The ice layer on the surface will break and be blown away by the airflow. Airbag deicing can easily destroy the aerodynamic shape and increase resistance, and it is not thorough. 4. Electric thermal anti-icing is to embed strip-shaped, filament-shaped or film-shaped heating elements into the structure of the aircraft's parts that are prone to ice formation, and use electrical heating to prevent and remove ice. Electric thermal anti-icing and deicing has both anti-icing and deicing functions, with low energy consumption, good deicing effect and easy control. It has become an important development trend of anti-icing / deicing systems. Electric thermal anti-icing / deicing technology is to install an electric heating device inside the outer skin. After electrical heating, the heat is transmitted "from the inside out", melting the ice layer attached to the surface of the fuselage, causing it to "desorb".
[0004] The physical mechanism of the aircraft electric heating anti-icing / de-icing system is the Joule heating effect of the electric heating material when it is powered on, and its core component is the electric heating body. The electric heating materials commonly used in the currently disclosed patents 201720077351.1 and 201720078408.X are mostly metal alloys, thermistor ceramics and conductive fibers. There are differences in expansion coefficients and high interface thermal resistance between the metal electric heating body and the body structure such as the insulation layer, which are prone to high thermal stress and structural thermal mismatch; thermistor ceramics are highly brittle and have poor processing performance, making it difficult to meet the requirements of aviation materials for impact resistance and fatigue resistance; conductive fibers have good flexibility, but their uniformity is difficult to control, and they are prone to local overheating that affects temperature control.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, so as to at least solve one of the technical problems existing in the prior art. The preparation method provided by the present invention applies nano-carbon material to fiber cloth to make the material generate heat and conduct heat more uniformly.
[0007] A second object of the present invention is to provide an electrothermal material prepared by a method for preparing an electrothermal material with high electrical contact matching for a load-bearing deicing integrated composite wing.
[0008] A third object of the present invention is to provide an application of an electric heating material in the preparation of an electric heating element.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, the present invention provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, comprising the following steps:
[0011] Applying nano-carbon material to a fiber cloth formed of conductive fibers, then sandwiching the fiber cloth in a water-soluble resin, attaching electrodes and pressing to obtain the electrothermal material;
[0012] Wherein, the nano-carbon material includes carbon nanotubes, graphene oxide and carbon powder;
[0013] After applying the nano-carbon material to the fiber cloth, the fiber cloth is sequentially subjected to a reducing agent application and a drying process before being sandwiched between the fiber cloth and the water-soluble resin.
[0014] Further, the carbon nanotubes include at least one of oxidized carbon nanotubes and carbon nanotube powder;
[0015] Preferably, the mass ratio of the oxidized carbon nanotubes, the oxidized graphene, the carbon nanotube powder and the carbon powder is 2:2:1:1-3:3:1:1;
[0016] Preferably, the diameter of the oxidized carbon nanotube is 10-20 nm, the diameter of the graphene oxide is 1-3 μm, the diameter of the carbon nanotube powder is 10-20 nm, and the diameter of the carbon powder is 20-30 nm;
[0017] Preferably, the applying of the nano-carbon material to the fiber cloth formed of the conductive fibers comprises: dispersing the formulated amounts of oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in water to obtain oxidized carbon nanotube suspension, graphene oxide suspension, carbon nanotube powder suspension and carbon powder suspension, and then applying the oxidized carbon nanotube suspension, carbon nanotube powder suspension and carbon powder suspension to the fiber cloth, and then applying the graphene oxide suspension to the fiber cloth;
[0018] Preferably, the concentrations of the oxidized carbon nanotube suspension, the oxidized graphene suspension, the carbon nanotube powder suspension and the carbon powder suspension are all 0.5-0.7 mg / mL.
[0019] Further, the oxidized carbon nanotube suspension, the oxidized graphene suspension, the carbon nanotube powder suspension and the carbon powder suspension are applied to the fiber cloth by spraying;
[0020] Preferably, each suspension is sprayed evenly 5-10 times.
[0021] Further, the conductive fibers include carbon fibers;
[0022] Preferably, carbon fiber cloth is obtained by weaving carbon fiber.
[0023] Further, the water-soluble resin includes a water-soluble alkyd resin;
[0024] Preferably, the electrode spacing is 70-75 mm;
[0025] Preferably, the rolling temperature is 70-130° C. and the roll gap is 0.4-0.5 mm.
[0026] Further, the reducing agent includes ascorbic acid solution;
[0027] Preferably, the mass ratio of the solute in the reducing agent to the nano-carbon material is 0.1:1-5:1;
[0028] Preferably, the concentration of the reducing agent is 50-3500 mg / L;
[0029] Preferably, the reducing agent is applied to the fiber cloth by spraying;
[0030] Preferably, the drying process is carried out at a temperature of 40-60°C and for a time of 20-24 hours.
[0031] Furthermore, before applying the nano-carbon material to the fiber cloth, the fiber cloth is subjected to a desizing treatment;
[0032] Preferably, the desizing treatment adopts Soxhlet extraction method. In a second aspect, the present invention provides an electrothermal material prepared by the method for preparing the high electrical contact matching electrothermal material for load-bearing and deicing integrated composite wing.
[0033] In a third aspect, the present invention provides an application of an electric heating material in preparing an electric heating element.
[0034] Furthermore, the electric heating element is a sheet-layer structure.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention provides a method for preparing a high-electrical contact matching electrothermal material for a load-bearing and deicing integrated composite wing. The fiber cloth formed by conductive fibers is used as the toughening phase and main conductive phase of the material, which plays the role of a load-bearing reinforcement and a main conductor with low resistivity. Nano-carbon material is used as the conductive and thermally conductive reinforcing phase, wherein carbon nanotubes are one-dimensional conductive and thermally conductive reinforcing phases, graphene oxide is two-dimensional conductive and thermally conductive reinforcing phases, and carbon powder is three-dimensional conductive and thermally conductive reinforcing phases. By applying the nano-carbon material to the fiber cloth, the material can achieve a more uniform heat and thermal conductivity effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 A schematic flow chart of a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing provided by the present invention;
[0039] Figure 2 This is a schematic diagram of the electrode patch position of Example 1 of the present invention.
[0040] Icon: 1-carbon fiber cloth; 2-copper electrode. DETAILED DESCRIPTION
[0041] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0042] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The first aspect of the present invention provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, comprising the following steps:
[0044] Applying nano-carbon material to a fiber cloth formed of conductive fibers, then sandwiching the fiber cloth in a water-soluble resin, attaching electrodes and pressing to obtain the electrothermal material;
[0045] Wherein, the nano-carbon material includes carbon nanotubes, graphene oxide and carbon powder;
[0046] After applying the nano-carbon material to the fiber cloth, the fiber cloth is sequentially subjected to a reducing agent application and a drying process before being sandwiched between the fiber cloth and the water-soluble resin.
[0047] The present invention provides a method for preparing a high-electrical contact matching electrothermal material for a load-bearing and deicing integrated composite wing. The fiber cloth formed by conductive fibers is used as the toughening phase and main conductive phase of the material, which plays the role of a load-bearing reinforcement and a main conductor with low resistivity. Nano-carbon material is used as the conductive and thermally conductive reinforcing phase, wherein carbon nanotubes are one-dimensional conductive and thermally conductive reinforcing phases, graphene oxide is two-dimensional conductive and thermally conductive reinforcing phases, and carbon powder is three-dimensional conductive and thermally conductive reinforcing phases. By applying the nano-carbon material to the fiber cloth, the material can achieve a more uniform heat and thermal conductivity effect.
[0048] In some preferred embodiments, the carbon nanotubes include at least one of oxidized carbon nanotubes and carbon nanotube powder;
[0049] Preferably, the mass ratio of the oxidized carbon nanotubes, the oxidized graphene, the carbon nanotube powder and the carbon powder is 2:2:1:1-3:3:1:1, for example, 2:2:1:1, 2.5:2.5:1:1, 3:3:1:1, etc.;
[0050] Preferably, the diameter of the oxidized carbon nanotube is 10-20nm, for example, it can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, etc.; the diameter of the graphene oxide sheet is 1-3μm, for example, it can be 1μm, 2μm, 3μm, etc.; the diameter of the carbon nanotube powder is 10-20nm, for example, it can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, etc.; the diameter of the carbon powder is 20-30nm, for example, it can be 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, etc.;
[0051] Preferably, the applying of the nano-carbon material to the fiber cloth formed of the conductive fibers comprises: dispersing the formulated amounts of oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in water to obtain oxidized carbon nanotube suspension, graphene oxide suspension, carbon nanotube powder suspension and carbon powder suspension, and then applying the oxidized carbon nanotube suspension, carbon nanotube powder suspension and carbon powder suspension to the fiber cloth, and then applying the graphene oxide suspension to the fiber cloth;
[0052] Preferably, the concentrations of the oxidized carbon nanotube suspension, the oxidized graphene suspension, the carbon nanotube powder suspension and the carbon powder suspension are all 0.5-0.7 mg / mL, for example, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL and the like.
[0053] In the present invention, it is preferred to use a spraying method to introduce a one-dimensional and two-dimensional conductive and thermally conductive enhancing phase into the main conductive phase, with carbon nanotubes as the one-dimensional conductive and thermally conductive enhancing phase and graphene oxide as the two-dimensional conductive and thermally conductive enhancing phase. The conductive and thermally conductive enhancing phase is filled into the fiber bundles by spraying to make the thermal conductivity of the material more uniform.
[0054] In the present invention, the above carbon nanomaterials are introduced in batches. First, nano-scale oxidized carbon nanotubes, carbon nanopowder tubes and carbon powder are introduced to fill the gaps in the fiber bundles, and then micron-scale graphene oxide is introduced to fill the gaps between the fiber bundles.
[0055] In some preferred embodiments, the oxidized carbon nanotube suspension, the oxidized graphene suspension, the carbon nanotube powder suspension, and the carbon powder suspension are applied to the fiber cloth by spraying;
[0056] Preferably, each suspension is sprayed evenly 5-10 times.
[0057] In the present invention, an electric spray gun is used to evenly spray the surface of the carbon fiber cloth, and the drying method is natural air drying. After air drying, the spraying operation is repeated, and the number of spraying times of each suspension is controlled at 5-10 times, for example, it can be 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, etc.
[0058] In some preferred embodiments, the conductive fibers include carbon fibers;
[0059] Preferably, carbon fiber cloth is obtained by weaving carbon fiber, and the size of the carbon fiber cloth is 100×60 mm.
[0060] In the present invention, continuous fibers (specifically carbon fibers) are used as the toughening phase and main conductive phase of the electric heating material.
[0061] In some preferred embodiments, before applying the nano-carbon material to the fiber cloth, the fiber cloth is subjected to a desizing treatment;
[0062] In the present invention, the desizing treatment is preferably performed by Soxhlet extraction. The surface of commercially available carbon fibers is coated with a layer of sizing agent. The desizing treatment of the carbon fiber cloth by Soxhlet extraction can remove the sizing agent on the surface of the carbon fibers and improve their conductivity.
[0063] In some preferred embodiments, before compounding with the water-soluble resin, the preparation method further comprises: applying a reducing agent and drying to the fiber cloth on which the nano-carbon material is deposited;
[0064] Preferably, the reducing agent is applied to the fiber cloth by spraying;
[0065] Preferably, the reducing agent comprises an ascorbic acid solution;
[0066] Preferably, the concentration of the reducing agent is 50-3500 mg / L; for example, it can be 50 mg / L, 100 mg / L, 500 mg / L, 1000 mg / L, 3000 mg / L, 3500 mg / L, etc.;
[0067] Preferably, the mass ratio of the solute in the reducing agent to the nano-carbon material is 0.1:1-5:1, for example, it can be 0.1:1, 1:1, 2:1, 3:1, 4:1, 5:1, etc.
[0068] Preferably, the drying temperature is 40-60°C, for example, 40°C, 50°C, 60°C, etc.
[0069] In the present invention, in order to obtain better conductivity, a reducing agent is used to reduce the carbon fiber cloth deposited with oxidized carbon nanomaterials, and the reducing agent reduces oxidized carbon nanotubes and graphene oxide to obtain reduced oxidized carbon nanomaterials, wherein the reducing agent is green and harmless ascorbic acid. After the reduction is completed, the carbon fiber cloth is washed with deionized water and placed in a vacuum oven for drying to obtain a heating plate.
[0070] In some preferred embodiments, the water-soluble resin includes a self-drying water-soluble alkyd resin;
[0071] Preferably, the electrode spacing is 70-75 mm, for example, 70 mm, 71 mm, 72 mm, 73 mm, 74 mm, 75 mm, etc.; the electrodes are preferably copper electrodes;
[0072] Preferably, the rolling temperature is 70-130°C, for example, 70°C, 80°C, 90°C, 100°C, 115°C, 120°C, 130°C, etc.; the roller gap is 0.4-0.5mm, for example, 0.4mm, 0.5mm, etc.
[0073] In the present invention, water-soluble resin is used for packaging, and the electric heating sheet obtained after the reduction step is sandwiched in an alkyd resin sheet, and copper electrodes are attached and then pressed, and the electric heating material is prepared by a dry prepreg method. The electric heating material is a continuous fiber reinforced conductive resin-based composite material prepreg.
[0074] A second aspect of the present invention provides an electrothermal material prepared by a method for preparing an electrothermal material with high electrical contact matching for a load-bearing and deicing integrated composite wing.
[0075] A third aspect of the present invention provides an application of an electrothermal material in the preparation of an electrothermal element, wherein the electrothermal element is a sheet-layer structure.
[0076] The electric heating element in the present invention is a high-electric contact matching electric heating element for load-bearing / deicing integrated composite wing, with carbon fiber as the structural toughening phase and the main conductive phase, introducing a one-dimensional and two-dimensional conductive reinforcement phase, and bonding and encapsulating with a water-soluble resin to form a sheet structure. The sheet structure is a single-layer structure, and the structural toughening phase and the main conductive phase of the sheet structure are carbon fiber cloth woven from carbon fiber, which plays the role of a load-bearing reinforcement and a main conductor with low resistivity. A one-dimensional and two-dimensional conductive and thermal conductive reinforcement phase is introduced into the main conductive phase by a spraying method, and after spraying, it is bonded and encapsulated with a water-soluble resin to form a prepreg, which is convenient for cutting and cutting to prepare an integrated composite wing. Compared with the prior art, the product produced by the present invention has the advantages of lightweight, high load-bearing, and a single-layer structure. The preparation method has a systematic and industrialized production and an efficient preparation mode, and is also suitable for the manufacture of electric heating elements for load-bearing / anti-deicing integrated composite wings of aircraft of any size.
[0077] Furthermore, the present invention provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, such as Figure 1 As shown, the specific steps include:
[0078] (1) Select carbon fiber cloth woven with carbon fiber, the size of the carbon fiber cloth is 100×60mm, and the carbon fiber cloth is desizing by Soxhlet extraction method. The specific operation of the extraction method is as follows: take the cut carbon fiber cloth, wrap it properly with filter paper and absorbent cotton, and put it into the extraction tube of Soxhlet extractor, add 200mL acetone in the extraction bottle, and extract at 75-80℃ for 72h. After the reaction is completed, take out the carbon fiber cloth, wash it with anhydrous ethanol and deionized water respectively, and put it into a 60℃ oven to dry for use;
[0079] (2) Dispersing the formulated amounts of oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in deionized water respectively, preparing oxidized carbon nanotube suspension, graphene oxide suspension, carbon nanotube powder suspension and carbon powder suspension of certain concentrations respectively by ultrasonic stirring, then applying the oxidized carbon nanotube suspension, carbon nanotube powder suspension and carbon powder suspension to the fiber cloth, and then applying the graphene oxide suspension to the fiber cloth.
[0080] (3) using an electric spray gun to evenly spray a mixture of an oxidized carbon nanotube suspension, a carbon nanotube powder suspension and a carbon powder suspension on the surface of the carbon fiber cloth, and then spraying the oxidized graphene suspension, and drying by natural air drying. After air drying, the spraying operation is repeated, and the total number of spraying times is controlled to be 5-10 times;
[0081] (4) Then, a reducing agent is used to reduce the carbon fiber cloth introduced with the oxidized carbon nanomaterial, ascorbic acid is weighed, dissolved in deionized water, and introduced into the carbon fiber cloth by spraying. After two hours, the reduction is completed, and the carbon fiber cloth is washed with deionized water, and placed in a vacuum oven at 40-60° C. for 20-24 hours to obtain an electric heater;
[0082] (5) The electric heating plate obtained in step (4) is sandwiched between two pieces of coated paper containing alkyd resin, copper electrodes are attached, and then placed in a double-roll rolling mill. After the rolling is completed, a continuous fiber reinforced conductive resin-based composite material prepreg, i.e., an electric heating material, is obtained.
[0083] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0084] Example 1
[0085] This embodiment provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, comprising the following steps:
[0086] (1) Select carbon fiber cloth woven with carbon fiber, the size of the carbon fiber cloth is 100×60mm, and the carbon fiber cloth is desizing treated by Soxhlet extraction method. The specific operation of Soxhlet extraction method is as follows: take the cut carbon fiber cloth, wrap it properly with filter paper and absorbent cotton, and put it into the extraction tube of Soxhlet extractor, add 200mL acetone in the extraction bottle, and extract at 75-80℃ for 72h. After the reaction is completed, take out the carbon fiber cloth, wash it with anhydrous ethanol and deionized water respectively, and put it into a 60℃ oven to dry for use;
[0087] (2) weighing oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in a mass ratio of 2.5:2.5:1:1, dispersing the oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in deionized water, respectively, and preparing oxidized carbon nanotube suspensions, graphene oxide suspensions, carbon nanotube powder suspensions and carbon powder suspensions of certain concentrations by ultrasonic stirring, wherein the concentrations of the oxidized carbon nanotube suspensions, graphene oxide suspensions, carbon nanotube powder suspensions and carbon powder suspensions are all 0.6 mg / mL;
[0088] Among them, the diameter of the oxidized carbon nanotube is 15nm, the diameter of the graphene oxide sheet is 2μm, the diameter of the carbon nanotube powder is 15nm, and the diameter of the carbon powder is 25nm;
[0089] (3) using an electric spray gun to evenly spray a mixture of an oxidized carbon nanotube suspension, a carbon nanotube powder suspension and a carbon powder suspension on the surface of the carbon fiber cloth, and then spraying the oxidized graphene suspension. After the spraying is completed, it is naturally air-dried for 24 hours. After air-drying, the above-mentioned oxidized carbon nanotube suspension, carbon nanotube powder suspension, carbon powder suspension and graphene oxide suspension are sprayed again, and the total number of spraying times is controlled to 8 times;
[0090] (4) Then, a reducing agent is used to reduce the carbon fiber cloth into which the oxidized carbon nanomaterials are introduced, ascorbic acid is weighed, dissolved in deionized water, and introduced into the carbon fiber cloth by spraying. After two hours, the reduction is completed, and the cloth is washed with deionized water, and placed in a vacuum oven at 50° C. for 22 hours to obtain an electric heater, wherein the ratio of the mass of ascorbic acid to the mass sum of the oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder is 3:1, and the concentration of the reducing agent is 2000 mg / L;
[0091] (5) sandwiching the electric heating plate obtained in step (4) between two coated papers containing a self-drying alkyd resin, attaching copper electrodes (electrode spacing 73 mm), and then placing them in a double-roll mill (rolling temperature 100° C., roller gap 0.45 mm), and obtaining a continuous fiber reinforced conductive resin-based composite material prepreg, i.e., an electric heating material, after the rolling is completed;
[0092] Among them, Figure 2As shown, the copper electrode is arranged along the width direction of the carbon fiber cloth 1 (i.e., parallel to the 60mm side direction of the carbon fiber cloth 1), two copper electrodes 2 are arranged with a spacing of 73mm, and the two electrodes are centered on the 100mm side of the carbon fiber cloth 1. The length of the copper electrode 2 is 80-85mm and the width is 8-10mm.
[0093] Example 2
[0094] This embodiment provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, comprising the following steps:
[0095] (1) Select carbon fiber cloth woven with carbon fiber, the size of the carbon fiber cloth is 100×60mm, and the carbon fiber cloth is desizing treated by Soxhlet extraction method. The specific operation of Soxhlet extraction method is as follows: take the cut carbon fiber cloth, wrap it properly with filter paper and absorbent cotton, and put it into the extraction tube of Soxhlet extractor, add 200mL acetone in the extraction bottle, and extract at 75-80℃ for 72h. After the reaction is completed, take out the carbon fiber cloth, wash it with anhydrous ethanol and deionized water respectively, and put it into a 60℃ oven to dry for use;
[0096] (2) weighing oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in a mass ratio of 2:2:1:1, dispersing the oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in deionized water, respectively, and preparing oxidized carbon nanotube suspensions, graphene oxide suspensions, carbon nanotube powder suspensions and carbon powder suspensions of certain concentrations by ultrasonic stirring, wherein the concentrations of the oxidized carbon nanotube suspensions, graphene oxide suspensions, carbon nanotube powder suspensions and carbon powder suspensions are all 0.7 mg / mL;
[0097] Among them, the diameter of the oxidized carbon nanotube is 10nm, the diameter of the oxidized graphene sheet is 1μm, the diameter of the carbon nanotube powder is 10nm, and the diameter of the carbon powder is 30nm;
[0098] (3) using an electric spray gun to evenly spray a mixture of an oxidized carbon nanotube suspension, a carbon nanotube powder suspension and a carbon powder suspension on the surface of the carbon fiber cloth, and then spraying the oxidized graphene suspension. After the spraying is completed, it is naturally air-dried for 24 hours. After air-drying, the above-mentioned oxidized carbon nanotube suspension, carbon nanotube powder suspension, carbon powder suspension and graphene oxide suspension are repeated. The total number of spraying times is controlled to 5 times;
[0099] (4) Then, a reducing agent is used to reduce the carbon fiber cloth introduced with the oxidized carbon nanomaterials, ascorbic acid is weighed, dissolved in deionized water, and introduced into the carbon fiber cloth by spraying. After two hours, the reduction is completed, and the cloth is washed with deionized water, and placed in a vacuum oven at 40° C. for 24 hours to obtain an electric heater, wherein the ratio of the mass of ascorbic acid to the mass sum of the oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder is 0.1:1, and the concentration of the reducing agent is 50 mg / L;
[0100] (5) sandwiching the electric heating sheet obtained in step (4) between two pieces of coated paper containing a self-drying alkyd resin, attaching copper electrodes (electrode spacing 70 mm), and then placing it in a double-roll mill (rolling temperature 70° C., roller gap 0.5 mm), and after the rolling is completed, a continuous fiber reinforced conductive resin-based composite material prepreg, i.e., an electric heating material, is obtained;
[0101] Among them, the copper electrode is arranged along the width direction of the carbon fiber cloth (i.e. parallel to the 60mm side direction of the carbon fiber cloth). There are two copper electrodes with a spacing of 70mm. The two electrodes are centered on the 100mm side of the carbon fiber cloth. The length of the electrode is 80-85mm and the width is 8-10mm.
[0102] Example 3
[0103] This embodiment provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, comprising the following steps:
[0104] (1) Select carbon fiber cloth woven with carbon fiber, the size of the carbon fiber cloth is 100×60mm, and the carbon fiber cloth is desizing treated by Soxhlet extraction method. The specific operation of Soxhlet extraction method is as follows: take the cut carbon fiber cloth, wrap it properly with filter paper and absorbent cotton, and put it into the extraction tube of Soxhlet extractor, add 200mL acetone in the extraction bottle, and extract at 75-80℃ for 72h. After the reaction is completed, take out the carbon fiber cloth, wash it with anhydrous ethanol and deionized water respectively, and put it into a 60℃ oven to dry for use;
[0105] (2) weighing oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in a mass ratio of 3:3:1:1, dispersing the oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in deionized water, respectively, and preparing oxidized carbon nanotube suspensions, graphene oxide suspensions, carbon nanotube powder suspensions and carbon powder suspensions of certain concentrations by ultrasonic stirring, wherein the concentrations of the oxidized carbon nanotube suspensions, graphene oxide suspensions, carbon nanotube powder suspensions and carbon powder suspensions are all 0.5 mg / mL;
[0106] Among them, the diameter of the oxidized carbon nanotube is 20nm, the diameter of the oxidized graphene sheet is 3μm, the diameter of the carbon nanotube powder is 20nm, and the diameter of the carbon powder is 20nm;
[0107] (3) using an electric spray gun to evenly spray the surface of the carbon fiber cloth with a sheet diameter of 2 μm, and air-drying it for 24 hours. After air-drying, repeat the spraying operation of the above-mentioned carbon nanotube suspension, carbon nanotube powder suspension, carbon powder suspension, and graphene oxide suspension, and the total number of spraying times is controlled within 10 times;
[0108] (4) Then, the carbon fiber cloth introduced with the oxidized carbon nanomaterial is reduced by a reducing agent, ascorbic acid is weighed, dissolved in deionized water, and introduced into the carbon fiber cloth by spraying. After two hours, the reduction is completed, and the cloth is washed with deionized water, and placed in a vacuum oven at 60° C. for 20 hours to obtain an electric heater, wherein the ratio of the mass of ascorbic acid to the mass sum of the oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder is 5:1, and the concentration of the reducing agent is 3500 mg / L;
[0109] (5) sandwiching the electric heating sheet obtained in step (4) between two coated papers containing a self-drying alkyd resin, attaching copper electrodes (electrode spacing 75 mm), and then placing the electric heating sheet in a double-roll mill (rolling temperature 130° C., roller gap 0.4 mm), and obtaining a continuous fiber reinforced conductive resin-based composite material prepreg, i.e., an electric heating material, after the rolling is completed;
[0110] Among them, the copper electrode is arranged along the width direction of the carbon fiber cloth (i.e. parallel to the 60mm side direction of the carbon fiber cloth). There are two copper electrodes with a spacing of 75mm. The two electrodes are centered on the 100mm side of the carbon fiber cloth. The length of the electrode is 80-85mm and the width is 8-10mm.
[0111] Example 4
[0112] This embodiment provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing. The difference from Embodiment 1 is that the mass ratio of oxidized carbon nanotubes, oxidized graphene, carbon nanotube powder and carbon powder is 1:1:1:1, and the remaining steps are consistent with Embodiment 1.
[0113] Example 5
[0114] This embodiment provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing. The difference from Embodiment 1 is that the mass ratio of oxidized carbon nanotubes, oxidized graphene, carbon nanotube powder and carbon powder is 4:4:1:1, and the remaining steps are consistent with Embodiment 1.
[0115] Example 6
[0116] This embodiment provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, which differs from Embodiment 1 in that:
[0117] In step (3), the graphene oxide suspension is sprayed first, and then the carbon nanotube oxide suspension, the carbon nanotube powder suspension and the carbon powder suspension are sprayed; the remaining steps are consistent with Example 1.
[0118] Example 7
[0119] This embodiment provides a method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, which differs from Embodiment 1 in that:
[0120] In step (2), the oxidized carbon nanotube suspension, the carbon nanotube powder suspension and the carbon powder suspension are sequentially sprayed onto the fiber cloth, and then the oxidized graphene suspension is sprayed onto the fiber cloth;
[0121] The other steps are consistent with those in Example 1.
[0122] Application Examples 1-7
[0123] Application Examples 1-7 use the electric heating materials prepared in Examples 1-7 to prepare electric heating elements.
[0124] Comparative Example 1
[0125] This comparative example provides an electrothermal material, which differs from Example 1 in that: in step (2), graphene oxide and carbon powder are weighed in a mass ratio of 5:2 and dispersed in deionized water; the remaining steps are consistent with Example 1.
[0126] Comparative Example 2
[0127] This comparative example provides an electrothermal material, which differs from Example 1 in that: in step (2), oxidized carbon nanotubes, carbon nanotube powder and carbon powder are weighed in a mass ratio of 5:1:1 and dispersed in deionized water; the remaining steps are consistent with Example 1.
[0128] Comparative Example 3
[0129] This comparative example provides an electrothermal material, which differs from Example 1 in that: in step (2), oxidized carbon nanotubes, oxidized graphene, and carbon nanotube powder are weighed in a mass ratio of 2.5:2.5:2 and dispersed in deionized water; the remaining steps are consistent with Example 1.
[0130] Comparative Example 4
[0131] This comparative example provides an electric heating material, which differs from Example 1 in that step (4) is not performed, and the remaining steps are consistent with Example 1.
[0132] Comparative Application Examples 1-4
[0133] Comparative Application Examples 1-4 respectively use the electric heating materials prepared in Comparative Examples 1-4 to prepare electric heating elements.
[0134] Test Case
[0135] Test method:
[0136] Tear off the coating paper of the continuous fiber reinforced conductive resin-based composite material prepreg, sandwich it between two glass fiber prepregs, and obtain the continuous fiber reinforced conductive resin-based composite material by hot pressing. The hot pressing process parameters are 100-130℃, 2-3MPa, 1h. Connect the DC power supply, adjust the voltage to 100-120V, and after reaching a stable state, observe the voltage and current, and calculate the conductivity of the material according to the material size. Adjust the voltage to keep the temperature of the material at 50-55℃, use an infrared thermal imager to detect the surface temperature of the material, obtain the temperature distribution diagram, and then calculate the maximum temperature difference on the surface.
[0137] Test samples: The electric heating elements prepared in Application Examples 1-7 and the electric heating elements prepared in Comparative Application Examples 1-4 were used as samples.
[0138] The test results are shown in Table 1.
[0139] Table 1
[0140]
[0141] It can be seen from the data in Table 1 that the carbon nanomaterials in the embodiment of the present invention are oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder, and when the ratio thereof is in the range of 2:2:1:1-3:3:1:1, the material has high electrical conductivity, and its corresponding heating rate is good, the temperature difference is small, and the heating uniformity is good; at the same time, by comparing the data of Application Example 4 and Application Example 1, it can be seen that the comprehensive performance of the carbon fiber cloth deposited with oxidized carbon nanomaterials reduced by a reducing agent is stronger.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high electrical contact matching electrothermal material for a load-bearing deicing integrated composite wing, characterized in that: The following steps are involved: Applying nano-carbon material to a fiber cloth formed of conductive fibers, then sandwiching the fiber cloth in a water-soluble resin, attaching electrodes and pressing to obtain the electrothermal material; Wherein, the nano-carbon material includes carbon nanotubes, graphene oxide and carbon powder; After applying the nano-carbon material to the fiber cloth, the fiber cloth is sequentially subjected to a reducing agent application and a drying process before being sandwiched between the fiber cloth and the water-soluble resin.
2. The method for preparing high electrical contact matching electrothermal material for load-bearing deicing integrated composite wing according to claim 1 is characterized in that: The carbon nanotubes include at least one of oxidized carbon nanotubes and carbon nanotube powder; Preferably, the mass ratio of the oxidized carbon nanotubes, the oxidized graphene, the carbon nanotube powder and the carbon powder is 2:2:1:1-3:3:1:1; Preferably, the diameter of the oxidized carbon nanotube is 10-20 nm, the diameter of the graphene oxide is 1-3 μm, the diameter of the carbon nanotube powder is 10-20 nm, and the diameter of the carbon powder is 20-30 nm; Preferably, the applying of the nano-carbon material to the fiber cloth formed of the conductive fibers comprises: dispersing the formulated amounts of oxidized carbon nanotubes, graphene oxide, carbon nanotube powder and carbon powder in water to obtain oxidized carbon nanotube suspension, graphene oxide suspension, carbon nanotube powder suspension and carbon powder suspension, and then applying the oxidized carbon nanotube suspension, carbon nanotube powder suspension and carbon powder suspension to the fiber cloth, and then applying the graphene oxide suspension to the fiber cloth; Preferably, the concentrations of the oxidized carbon nanotube suspension, the oxidized graphene suspension, the carbon nanotube powder suspension and the carbon powder suspension are all 0.5-0.7 mg / mL.
3. The method for preparing high electrical contact matching electrothermal material for load-bearing and deicing integrated composite wing according to claim 2 is characterized in that: Applying the oxidized carbon nanotube suspension, the oxidized graphene suspension, the carbon nanotube powder suspension and the carbon powder suspension to the fiber cloth by spraying; Preferably, each suspension is sprayed evenly 5-10 times.
4. The method for preparing high electrical contact matching electrothermal material for load-bearing and deicing integrated composite wing according to claim 1, characterized in that: The conductive fibers include carbon fibers; Preferably, carbon fiber cloth is obtained by weaving carbon fiber.
5. The method for preparing high electrical contact matching electrothermal material for load-bearing and deicing integrated composite wing according to claim 1, characterized in that: The water-soluble resin includes a water-soluble alkyd resin; Preferably, the electrode spacing is 70-75 mm; Preferably, the rolling temperature is 70-130° C. and the roll gap is 0.4-0.5 mm.
6. The method for preparing high electrical contact matching electrothermal material for load-bearing and deicing integrated composite wing according to claim 1, characterized in that: The reducing agent includes an ascorbic acid solution; Preferably, the mass ratio of the solute in the reducing agent to the nano-carbon material is 0.1:1-5:1; Preferably, the concentration of the reducing agent is 50-3500 mg / L; Preferably, the reducing agent is applied to the fiber cloth by spraying; Preferably, the drying process is carried out at a temperature of 40-60°C and for a time of 20-24 hours.
7. The method for preparing high electrical contact matching electrothermal material for load-bearing deicing integrated composite wing according to claim 1, characterized in that: Before applying the nano-carbon material to the fiber cloth, the fiber cloth is subjected to a desizing treatment; Preferably, the desizing treatment adopts Soxhlet extraction method.
8. The electrothermal material prepared by the method for preparing an electrothermal material with high electrical contact matching for a load-bearing and deicing integrated composite wing according to any one of claims 1 to 7.
9. Use of the electric heating material as claimed in claim 8 in preparing electric heating elements.
10. The use according to claim 9, characterized in that: The electric heating element is a sheet-layer structure.
Citation Information
Patent Citations
Aircraft anti -icing and de -icing 's electric heating unit
CN206602671U
Aircraft electricity anti -icing and de -icing electrical heating structure
CN206602672U
Preparation method of graphene composite conductive fiber
CN105484016A
Preparation method of interface layer of superhigh temperature thermal structure composite
CN106747671A
Method for preparing graphene column and carbon nano tube fiber reinforced SiCN composite
CN108101548A